The e-Learning Needs Analysis in Graduate Programs of Universitas Negeri Makassar - Nurhikmah Hasyim; Abdul Haling (Universitas Negeri Makassar, 2017)
This research aims to develop learning materials and tutorial videos e-learning for students of PPs UNM. Accurately, this research will produce learning materials, video tutorials, and scholarly articles. Product development refers to the ADDIE model (Analysis-Design-Develop-Implement-Evaluate) developed by Reiser and Mollenda in 1990. The research subject is graduate PPs UNM and the data gathering methods are documentation, interview, questionnaire, and tests, then analyzed by the descriptive qualitative method. In the first stage of research conducted analysis, i.e., identifying characteristics or profiles of prospective participants learn, identify gaps, and the identification of needs. The result shows, 1) characteristic of participants, i.e., in the range 25-35 years adult category, the respondent's gender dominated by women and respondents are dominated by kindergarten teacher/PAUD until lecturer, and they have a very high motivation to learn the program; 2) Some gap identify based on question form given to the respondents, i.e., they strongly agree with the application of e-learning-based lesson at school and University, but abilities and skills related to the program is still very limited; and 3) needed learning materials in the form of video tutorials that can help them to learn independently and master the lesson of e-learning based program.